TINJAUAN MOLEKULAR DAN ASPEK KLINIS RESISTENSI INSULIN - Sulistyoningrum, Evy (MANDALA of Health, 2010)
Insulin resistance is defined by an unresponsive condition in the target organ that normallyresponded to insulin hormone. Insulin resistance play a major role in many serious health problem such asmetabolic syndrome, type II diabetes, polycistic ovarii syndrome, cancer and cardiovascular diseases. Themechanism of insulin resistance is still unclearly understood. Researchers postulated two mechanism ofinsulin resistance, based on inflammatory theory and obesity theory. These two causes of insulin resistancehave different mechanism of action. Clinical diagnosis of insulin resistance can be performed by clampmethod and minimal model of frequency sampled intravenous glucose tolerance test (FSIVGTT) but thesegold standard diagnosis are very invasive. Non-invasive methods for diagnosing insulin resistance can beperformed by using various formulas derived from base examination in glucose and insulin plasma level.One of the formulas which have high sensitivity and specificity is HOMA-IR index (Homeostasis ModelAssessment-Insulin Resistance). Different characteristic of population required different cut-off fordetermining insulin resistant condition.